Precision method for the determination of neutrino mixing angle - Rusov, V.D.; Zelentsova, T.N.; Tarasov, V.A.; Shaaban, I. (Вопросы атомной науки и техники, 2001)
Based on the properties of the cascade statistics of reactor antineutrinos the effective method of neutrino oscillations searching is offered. The determination of physical parameters of this statistics, i.e., the average number of fissions and the average number of antineutrinos per fission, does not require a priori knowledge of geometry and characteristics of the detector, the reactor power and composition of nuclear fuel.